Nonlinear control of coal-fired steam power plants. (March 2017) - Alamoodi, Nahla; Daoutidis, Prodromos
Abstract: This work proposes a nonlinear control strategy for steam power plants that efficiently controls the superheated steam temperature while accommodating large and frequent variations in power demand. The variables to be controlled are the pressure in the boiler, power generation, and superheater/reheater temperatures. The proposed strategy decomposes the overall plant into three separate subsystems and applies decoupling with deadtime compensation for each one of them. The derived strategy is implemented within a MATLAB/Simulink environment for different setpoint tracking and disturbance rejection cases, showing excellent performance and robustness. Abstract : Highlights: A nonlinear control structure to regulate superheated steam temperature is proposed. The structure relies on decoupling of boiler pressure and steam temperature dynamics. The decoupling compensator allows the control of boiler pressure independently. Independent pressure control eliminates the inverse response of steam temperature. Decomposition of the power plant into subsystems lessens interactions among them.